Cents and sustainability : securing our common future by decoupling economic growth from environmental pressures - Smith, Michael H., 1969- (Online access with subscription: Proquest Ebook Central., 2010)
Cents and Sustainability is a clear-sighted response to the 1987 call by Dr Gro Brundtland in Our Common Future to achieve a new era of economic growth that is 'forceful and at the same time socially and environmentally sustainable'. The Brundtland Report argued that not only was it achievable, but that it was an urgent imperative in order to achieve a transition to sustainable development while significantly reducing poverty and driving 'clean and green' investment. With some still arguing for significantly slowing economic growth in order to reduce pressures on the environment, this new book.